Latent Toxoplasma gondii infection and associated risk factors among patients with chronic kidney disease: a registry-based study - Mahbobeh Montazeri; Mahdi Fakhar; Omid Sedighi; Atieh Makhlough; Rabeeh Tabaripour; Maryam Nakhaei; Mostafa Soleymani (BMC Nephrology)
Abstract Background Patients with chronic kidney disease (CKD) are susceptible to acquiring opportunistic parasites due to acquired immunodeficiency caused by uremia. Therefore, the present case–control study attempted to determine the prevalence of T. gondii infection and also associated risk factors among patients with CKD under hemodialysis and healthy controls who were registered at the Iranian National Registry Center for Toxoplasmosis (INRCT) in Mazandaran Province, northern Iran. Methods 212 cases with CKD and 200 healthy controls were enrolled in this study. Informed consent as well as a questionnaire were obtained from all subjects. Blood samples were collected from each participant and the serum was screened for anti-Toxoplasma antibodies (IgG and IgM). PCR assay was performed to detect circulating T. gondii in the blood samples of patients and controls using the primer pair targeting the RE gene. Results Out of 412 participants, 67.92% of patients and 15.5% of control subjects were positive for anti-Toxoplasma IgG, but all participants were negative for anti-Toxoplasma IgM. Also, considering PCR assays with RE target, the prevalence of T. gondii infection was 24.1% in case subjects, while none of the control subjects tested positive. Among the PCR positive, 34 (66.7%) had Toxoplasma IgG positivity. The results from the multiple multinomial logistic regression revealed that the seroprevalence of anti-T. gondii IgG antibodies in patients with CKD was 3.12 times higher than in healthy controls (OR = 3.12; 95% CI = 0.43, 14.8; P < 0.001). Also, there was a significant association between seroprevalence of T. gondii infection and age, having a cat at home, and level of glomerular filtration rate (GFR) in these patients. Conclusion Our findings demonstrate a highly significant association between latent T. gondii infection and CKD, mostly in the late stages. Thus, regular screening for T. gondii infection in these patients is strongly recommended to prevent the reactivation of latent infections. A combination of serological screening, chemoprophylaxis, and PCR follow-up for patients at risk of reactivation should effectively reduce the likelihood of latent infection reactivation. Clinical trial number Not applicable.